SERS using two-photon polymerized nanostructures for mycotoxin detection. Issue 24 (8th April 2020) - Liu, Qing; Vanmol, Koen; Lycke, Sylvia; Van Erps, Jürgen; Vandenabeele, Peter; Thienpont, Hugo; Ottevaere, Heidi
Abstract : Nano-pillar arrays are presented ranging from 200 nm to 600 nm as SERS substrates for mycotoxin detection, fabricated by two-photon polymerization. This versatile approach gives new opportunities for material characterization in chemical and biological applications. Abstract : Improved chemical- and bio-sensing with Surface Enhanced Raman Spectroscopy (SERS) requires nanostuctures that can be flexibly designed and fabricated with different physical and optical properties. Here, we present nano-pillar arrays ranging from 200 nm to 600 nm as SERS substrates for mycotoxin detection that are fabricated by means of two-photon polymerization. We built a nominal shape and a voxel-based model for simulating the enhancement of the electric field of the nano-pillar arrays using the Finite-Difference Time-Domain (FDTD) method. A new model was built based on the Atomic Force Microscopy (AFM) data obtained from the fabricated nanostructures and introduced into a FDTD model. We demonstrated the enhancement behavior by measuring the Raman spectrum of Rhodamine B solutions. Both the simulations and experimental results suggest that the 200 nm nano-pillar array has the highest Enhancement Factor (EF). Besides, we determined the limit of detection of the 200 nm pillar array by performing Raman measurements on Rhodamine B solutions with different concentrations. The detection limit of our 200 nm nano-pillar array is 0.55 μM. Finally we discriminated 1 ppm deoxynivalenol and 1.25 ppm fumonisin b1 in acetonitrile solutions by our SERS substrate in combination with principal component analysis. This versatile approach for SERS substrates fabrication gives new opportunities for material characterization in chemical and biological applications.